Reliability and security investigations on video streaming over satellite links - Ma, Ting (2015)
This thesis mainly presents three parts of studies, including video streaming over satellite reliability issue, preventing satellite system from denial of service (DoS) attacks and bitstream-oriented protection for the newly H.264/scalable video coding (SVC). The study of video streaming over satellite reliability issue is performed through video streaming experiments and simulations. A video streaming experiment over a satellite link for 24 days distributed over one year is performed to investigate the effects of rain fade. Based on the measurements, models for the relationships between rainfall rate, power level, packet loss, and video quality are proposed. Furthermore, for both uplink and downlink channel, an adaptive closed loop power control algorithm, with a proportional-integral-derivative (PID) controller is designed. This is used for the mitigation of the rain-induced attenuation in order to guarantee a certain level of quality of service (QoS) and quality of experience (QoE). Simulation results show the effectiveness of the proposed power control solution and its ability to sustain video quality levels in spite of rain fades. The aim of preventing satellite system from DoS attacks study is to improve its DoS attack detection efficiency. The proposed Rabin function protecting sequence number of each message is able to detect disassociation DoS attacks faster, for the first step of each communication session between network control center (NCC) and return channel satellite terminals (RCST) is the sequence number verification. The modeling of satellite system with Rabin function protection against disassociation Summary viii DoS attacks is proposed. We also provide modeling verifications by employing colored petri nets (CPN) tools. And simulation results show that our proposed method is efficient and practical. Further numerical analysis demonstrates the feasibility of the proposed scheme. The last part of study focuses on the H.264/SVC video security issue. An efficient bitstream-oriented protection scheme for the H.264/SVC bitstream is presented in a compression friendly and format compliant manner. The proposed scheme is performed based on network abstraction layer (NAL) units after video compression, so the solution is bitstream-oriented. For better computational efficiency, different computation-cost cryptographic algorithms are employed to different significant content levels of SVC to provide sufficient security. The I slice NAL units from the base layer of SVC bitstream are encrypted by the symmetric AES algorithm in cipher block chaining (CBC) mode. And the other NAL units are protected by simple CBCmode XOR cipher. Furthermore, a robust key management (key generation and distribution) mechanism is discussed to enhance security. The security analysis and simulation results further verify that the proposed methods can effectively protect the H.264/SVC bitstream at low computational cost. The thesis contributes to the understanding of rain attenuations to the video streaming over satellite links. The analytical models for rainfall rate, IP packet loss and received power level are derived for analysis rain attenuations on video quality. A PID controller that uses an adaptive closed loop power control approach in both uplink and downlink is proposed to overcome rain attenuation for video streaming via Ka-band satellite links. The effectiveness of our proposed scheme is also verified by using simulations. The harmful effect of DoS attacks to satellite system is presented in this thesis. Sequence number protected by Rabin function is proposed to detect the malicious DoS attacks more quickly. This thesis contributes to introducing a novel H.264/SVC protection scheme at the bitstream level. Different Summary ix complexity encryption algorithms to different important levels of the scalable video content are proposed. Sufficient protection is ensured and the computational cost is reduced. A key management scheme is developed on a layer basis to further improve the protection of the encryption keys used in AES and XOR algorithm.